STRATEGIES OF ACTORS IN THE REGULATION OF ACCES TO IMPORTED OLD VEHICLES IN THE CONTEXT OF CLIMATE WARMING IN IVORY COAST - KONE VAZOUMANA (Revue Internationale du Chercheur, 2025)
Ivory Coast issued law in december 2017 related to limitation of imported vehicles ages. The law went on in july 2018. The objectives of such investigations is to analyse the impact of these restrictions on importers and retailiers businesses in this sector. Otherwise, to reach such a goal, semi directives structured talks and groups focus were undertaken and individuals talks and focus group were undertaken with 33 persons in the district of Abidjan. The study of our talks revealed that limitation of imported vehicles ages stands in a context of executives aiming at organizing and regulating the reform, impact on importers activities, managers and retailers businesses and also in autonomous regulations to be adapted to the case. Otherwise, reconversion and association of lucratives activities as well as fraud and trespass the current Law helped by some cubious and armed forced agents stand as Key facts for adaptations strategies.